Exploración de Sentimientos, emociones, vivencias frente al Reasentamiento Involuntario por Causa de Minería Legal en Comunidades aledañas al complejo carbonífero del Cerrejón - La Guajira. (2021)
This research work is developed with the objective of exploring the experiences of involuntary resettlement, due to legal mining in Wayuu and Afro-descendant communities, near the coal complex, through the description of the experiences, of a perceptional determination at the social level and the description of the social impacts of resettlement in the communities. To achieve this, we worked methodologically as a qualitative cut, of phenomenological design, with primary sources from some settlers, which make up a sample of 20 people, 10 belonging to the Wayuu community. and 10 Belonging to the Afro-descendant ethnic group who, through life stories, and writing experiences, provide the necessary data to finalize it